Presacral tumor, experience of two cases in Mexico and review of the literature - A., Mauricio Gutierrez; M., Daniel I. Camacho; H., Jorge Leal; C., Kevin J. Fuentes (International Journal of Research in Medical Sciences, 2024)
Presacral or retrorectal tumors are rare, they can present different histologic strains and they can also be benign or malignant. These tumors represent a challenge for the surgeon due to their location in the presacral space and due to the low incidence and written information. Various surgical approaches have been described. We present the case of two patients who were diagnosed with presacral tumors (hamartoma and schwannoma) and who underwent a posterior approach for the removal of the tumors. There are several approaches for the treatment of presacral tumors, but in our experience, the posterior approach has shown adequate results without recurrence in the medium-term follow-up. The purpose of the manuscript is to document our experience in the management of two patients.